General strength and kinetics: fundamental to sprinting faster in cross country skiing? - Stöggl, T.; Müller, E.; Ainegren, M.; Holmberg, H. C. (Scandinavian Journal of Medicine & Science in Sports, 2011)
To determine relationships between general strength, maximal skiing speed (Vmax), pole and leg kinetics and kinematics, 16 male elite skiers underwent three Vmax tests in double poling, diagonal stride and V2 on a treadmill. The analyzed skiing speeds and leg and arm kinetics were among the highest ever recorded. Relationships between general strength exercises and Vmax were technique dependent. Power output in bench press and bench pull were related to Vmax in DP and diagonal stride, whereas each 1 repetition maximum was related to V2. Isometric squats were not associated with Vmax in all three techniques, whereas jump height and rate of force development during squat jump were. Analysis of kinetics and kinematics revealed that it was not exclusively the magnitude of applied forces during skiing, but the timing and proper instant of force application were major factors discriminating between faster and slower skiers. For all techniques, the faster skiers used different skiing strategies when approaching Vmax when compared with the slower skiers. General strength and power per se seem not to be major determinants of performance in elite skiers, whereas coordination of these capacities within the different and complex skiing movements seems to be the discriminating factor.